PERBANDINGAN PERIZINAN DALAM KELEMBAGAAN PERBANKAN SYARIAH DAN KONVENSIONAL - Sry Lestari (Institut Agama Islam Negeri Padngsidimpuan, 2016)
Since the appliance of UU no.7 1992 about Banking, the Dual Banking System is apply too. All institutions need to adjust their activites with the new paradigm. Central bank, bank of community credit (BPR) need procedure which set in banking constitution and procedure of licence from the start up, ownership, management until controlling is set by Indonesia Bank as central bank. However, the bank which run syariah pinciple will also controlled by Indonesia Bank accompanied by DSN and DPS.